Interactive Panel Summaries of the 2024 Voice AI Symposium - Bélisle-Pipon, Jean-Christophe; Anibal, James; Bahr, Ruth; Bedrick, Steven; Coleman, Oita; Dorr, David; Evans, Barbara J.; Fagherazzi, Guy; Gelbard, Alexander; Ghosh, Satrajit; Ho, Anita; Jackson, Christie; et al. (Frontiers in Digital Health, 2025)
The 2024 Voice AI Symposium presented by the Bridge2AI-Voice Consortium, was a 2-day event which took place May 1st-May 2nd in Tampa, FL. The event included four interactive panel sessions, which are summarized here. All four interactive panels featured an innovative format, designed to maximize engagement and facilitate deep discussions. Each panel began with a 45 min segment where moderators posed targeted questions to expert panelists, delving into complex topics within the field of voice AI. This was followed by a 45 min “stakeholder forum,” during which audience members asked questions and engaged in live interactive polls. Interactive polls stimulated meaningful conversation between panelists and attendees, and brought to light diverse viewpoints. Workshops were audio recorded and transcripts were assembled with assistance from generative A.I tools including Whisper Version 7.13.1 for audio transcription and ChatGPT version 4.0 for content summation. Content was then reviewed and edited by authors.